Voluntary disclosure of accounting ratios and firm-specific characteristics: the case of GCC - Shibly, Fatima (2020)
The purpose of this study is to investigate the voluntary disclosure of accounting ratios in the corporate annual reports of manufacturing firms in the Gulf Cooperation Council (GCC) and determines whether an association exists between voluntary disclosure and firm-specific characteristics namely, size, profitability, leverage, liquidity and efficiency.